Multipole analysis on protein charge distribution. - Chia, Zhong Yi. (2011)
The interactions in protein system are known to be very complicated. Extra attention should be paid to special cases where the interactions can be simplified such that the law of physics in proteins can be captured. A literature review on the protein force field was done so as to justify that the dominating guiding force is electrostatic effect. Therefore the focus of this project is on the guiding force in protein-protein / enzyme-substrate interaction.